Peran Media Pembelajaran Dalam Meningkatkan Kemampuan Bahasa Arab Siswa di Yayasan Pendidikan An - Nauri Madrasah Darul Madani - Hasibuan, Jamaluddin; S, Fahrurrozi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research discusses the role of learning media in improving students' Arabic language skills at the An-Nuari Madrasah Darul Madani Education Foundation. This research is intended to find out the role of learning in improving students' Arabic language skills and to find out the role of using learning media in improving abilities. Arabic language for students. This research uses descriptive qualitative research methods. This research uses primary data and secondary data. The research location was carried out at the An-Nuari Madrasah Darul Madani Education Foundation. The results of this research show that the role of learning media can improve students' Arabic language learning abilities. This was obtained through observing students' activities in the classroom during the learning process and through the results of students' daily evaluation tests after the learning process. The teaching staff at the An-Nuari Madrasah Darul Madani Education Foundation use learning media in the form of whiteboards, pictures, cards, objects inside and outside the classroom and textbooks. The supporting media provided by the school is Infocus in improving the Arabic language of students at the An-Nuari Madrasah Darul Madani Education Foundation.